Osteometric analysis of supraorbital foramen and notch in Malaysian crania - Ibrahim A.; Attalla S.M.; Alias A.; Swarhib M.; Bakar S.N.A.; Das S.; Nor F.M. (Innovare Academics Sciences Pvt. Ltd, 2024)
Indexed by SCOPUS